PROCEDURES OF FAIR DIVISION OF A SET OF INDIVISIBLE GOODS WITH MONEY - Marek Bożykowski (Decyzje, 2011)
The paper presents and compares four nonprobabilistic procedures of fair division of a set of indivisible goods with money: Original Knaster, Adjusted Knaster, Equal Shares and Second Prices. The last two are presented for the first time in the article. The analysis concerns the formal properties of those methods, namely: strong Pareto optimality, proportionality, envy-freeness, fairness, strategy-proofness and anonymity. Moreover, classes of situations in which those procedures meet aforementioned properties will be compared